Biofilm Disrupting Technology for Orthopedic Implants: What’s on the Horizon? - Connaughton, Alexander; Childs, Abby; Dylewski, Stefan; Sabesan, Vani J. (Frontiers in Medicine, 2014)
The use of orthopedic implants in joints has revolutionized the treatment of patients with many debilitating chronic musculoskeletal diseases such as osteoarthritis. However, the introduction of foreign material into the human body predisposes the body to infection. The treatment of these infections has become very complicated since the orthopedic implants serve as a surface for multiple species of bacteria to grow at a time into a resistant biofilm layer. This biofilm layer serves as a protectant for the bacterial colonies on the implant making them more resistant and difficult to eradicate when using standard antibiotic treatment. In some cases the use of antibiotics alone has even made the bacteria more resistant to treatment. (1-2) Thus, there has been surge in the creation of non-antibiotic anti-biofilm agents to help disrupt the biofilms on the orthopedic implants to help eliminate the infections. In this study we discuss infections of orthopedic implants in the shoulder then we review the main categories of anti-biofilm agents that have been used for the treatment of infections on orthopedic implants. Then we introduce some of the newer biofilm disrupting technology that has been studied in the past few years that may advance the treatment options for orthopedic implants in the future.